Implementation Of Telling Story Video Media In Teaching Listening Comprehension Class - Dwi Nur Hadiyansah; Dardiri Dardiri (Lembaga Pengembangan Kinerja Dosen, 2023)
The use of Video Telling Story Media is a method that is applied in the English Dormitory listening comprehension class. This research is qualitative research, by conducting descriptive analysis using primary data and secondary data. This study uses data collection methods in the form of interview, observation, and documentation using data analysis techniques in the form of reduction (data reduction), data display (presentation), and verification (conclusion). Based on the results of research obtained in research and discussion, it is known that the implementation of Media Video Telling Story has a good impact on students, Students' listening skills increased rapidly because in the videos they watched there were subtitles that helped students guess vocabulary that was not heard.